Patterns of Pediatric Cancers in Florida: 2000-2015 - Amin, Raid W.; Bohnert, Alexander; Banks, David (Statistics and Public Policy, 2019)
This study identifies pediatric cancer clusters in Florida for the years 2000-2015. Unlike previous publications on pediatric cancers in Florida, it draws upon an Environmental Protection Agency dataset on carcinogenic air pollution, the National Air Toxics Assessment, as well as more customary demographic variables (age, sex, race). The focus is upon the three most widely seen pediatric cancer types in the USA: brain tumors, leukemia, and lymphomas. The covariates are used in a Poisson regression to predict cancer incidence. The adjusted cluster analysis quantifies the role of each covariate. Using Florida Association of Pediatric Tumor Programs data for 2000-2015, we find statistically significant pediatric cancer clusters, but we cannot associate air pollution with the cancer incidence. Supplementary materials for this article are available online.
CRIS-Team WoS Importer:2019-06-18